The impact of Technium on the knowledge economy of South West Wales. - Gareth Huw Davies (2007)
This thesis investigates the impact of Technium in the development of the South West Wales Knowledge Economy. The Technium South West Wales network comprises of a set of business incubation and innovation Centres supporting enterprise in a range of high-growth sectors. The thesis acknowledges that Technium is a long-term initiative and the most meaningful benefits will follow in the future. However, it provides an understanding of the initiative's impact to date and how it is placed to support future development of the Knowledge Economy. Other studies examining the impact of incubation and science parks have traditionally focused on either economic impact or the development of the resident companies. This thesis investigates both aspects, together with the role of Technium in a Sub-Regional Innovation System. The economic impact aspect of the study examined Technium from its inception in 1999 through to 2008 when all Centres in the South West will be operational. It was found that the initiative has provided significant benefits to the region. Whereas previous studies had only examined job creation in tenant companies, this thesis presents how Technium has delivered a range of economic impacts during the construction phase and in subsequent operation. With regard to the development of innovation and knowledge-based enterprise, a survey involving questionnaires and interviews amongst Technium companies and other firms in the wider community has shown the relative performance of companies supported by the initiative. It is shown that Technium companies are growing faster, innovating more intensely and are engaged more strongly and extensively in networking and collaboration. The wider role of Technium has been investigated in a broad study of the regional Knowledge Economy. It is shown that the initiative is a component in a Sub-Regional Innovation System, linked with a variety of stakeholders in public, private and educations sectors.